THE INFLUENCE OF ENGLISH LITERATURE ON GLOBAL THOUGHT AND CULTURE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article explores the significant influence of English literature on global thought and culture. It examines how literary works written in English have transcended national boundaries to shape ideologies, inspire social and political change, and foster cross-cultural understanding. The review highlights the global reach of canonical authors, the role of literature in colonial and postcolonial contexts, and the emergence of diverse voices within the English literary tradition. Through education, media, and digital platforms, English literature continues to impact how people think, communicate, and relate to global issues. The discussion and analysis demonstrate that English literature remains a powerful force in shaping collective consciousness and cultural identity worldwide.